‘Tiny but Mighty’ Conversational Elements: Explicating Non-lexical Backchannels in Spoken Turkish - Kadriye AYTAÇ DEMİRÇİVİ; Hale IŞIK-GÜLER (Dilbilim Araştırmaları Dergisi)
This paper analyzes the functions of non-lexical backchannels in the Spoken Turkish Corpus and the differences in their use in naturally formed combinatory groups of gender and age (young-middle aged-elderly). Adopting a cyclic approach in the analysis of the 2231 non-lexical backchannels from the study corpus, two main and 16 sub-functions, eight of which are unique to this study and exhibit original dimensions have been identified. Results reveal that groups with female speakers and young speakers tend to use backchannels more for ‘approving the other speaker’, whereas groups with male speakers, middle-aged and elderly speakers tend to use backchannels more for ‘continuation of the conversation’. Despite these statistical tendencies, the findings suggest that when people have more in common and more interest in the given conversational topic, they use multifunctional non-lexical backchannels to construct meaning more cooperatively, regardless of gender and age-related variables.